Comparison of safety and effectiveness between phacoemulsification and suture less small incision procedures in Cataract surgery - Asma Aftab; Muhammad Imran Janjua; Yaseen Lodhi; Marrium Shafi; Saad Rauf Khan (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Cataract is major cause of preventable blindness, worldwide. Phacoemulsification and manual small incision are most common surgical methods of cataract. The objective of our study was to compare surgical outcomes and complications in phacoemulsification (Phaco) and manual small incision cataract surgery (MSICS) patientsMETHODOLOGY: A Prospective Observational study was conducted at Ophthalmology department of POF Hospital Wah Cantt, Pakistan. Study duration was 6 months (January 2020-June 2020). We calculated sample size of 30 cataract patients. Selection of cataract patients in OPD was done through non probability consecutive sampling technique. Afterwards, they were divided randomly into two different groups using lottery method; Group A patients cataract extraction was done with Phacoemulsification while in group B patients cataract extraction was done with small incision cataract surgery. Patients were followed for 5 weeks. Fisher-exact test and independent and paired T-test was applied to get statistically significant results. P value ≤0.05 was considered significant.RESULTS: Total 30 patients were included in study. There were 19(64.5%) male and 11(35.5%) female.  Mean age of patients was 48.3±7.5SD. There was a significant change in pre and post operative visual acuity in both groups (Group A p=0.000 and Group B p=0.000). MSICS showed high surgery duration as compared to phacoemulsification (29.6±1.5 vs 22.2±2.1, p=0.000).CONCLUSION: Phacoemulsification and Manual small incision cataract surgery are safe and clinically effective surgical techniques that did not show any difference in surgical outcomes. However, Phacoemulsification is associated with less post-operative complications as compared to MSICS.